Lucent technologies and DHL achieving 48 hours delivery lead time through business logistics partnership - Madhukar Kamath (2008)
The objective of this case is to demonstrate the synergy effects from the strategic alliance between Lucent Technologies and DHL. The case study discusses the problems and issues faced by Lucent, before choosing DHL as their global logistics partner, the challenges faced during the process of transition and managing post alliance relationship.